Monetising the impacts of waste incinerators sited on brownfield land using the hedonic pricing method. (March 2017) - Rivas Casado, Monica; Serafini, Jan; Glen, John; Angus, Andrew
Highlights: The impacts of incineration on property prices are different at each incinerator. The results show that some incinerators have increased the value of selected houses. Spatial planning seems to have mitigated some of the incinerators impacts. The negative impact of the incinerators ranged from 0.4% of the mean house price to 1.3%. These estimates fall in between the highest and lowest estimates from the literature. Abstract: In England and Wales planning regulations require local governments to treat waste near its source. This policy principle alongside regional self-sufficiency and the logistical advantages of minimising distances for waste treatment mean that energy from waste incinerators have been built close to, or even within urban conurbations. There is a clear policy and research need to balance the benefits of energy production from waste incinerators against the negative externalities experienced by local residents. However, the monetary costs of nuisance emissions from incinerators are not immediately apparent. This study uses the Hedonic Pricing Method to estimate the monetary value of impacts associated with three incinerators in England. Once operational, the impact of the incinerators on local house prices ranged from approximately 0.4% to 1.3% of the mean house price for the respective areas. Each of the incinerators studied had been sited on previously industrialised land to minimise overall impact. To an extent this was achieved and results support the effectiveness of spatial planning strategies to reduce the impact on residents. However, negative impacts occurred in areas further afield from the incinerator, suggesting that more can be done to minimise the impacts of incinerators. The results also suggest that in some case the incinerator increased the value of houses within a specified distance of incinerators under specific circumstances, which requires further investigation.